A Bibliometric Analysis of Ma‘Alim Al-Quran Wa Al-Sunnah Journal Published by USIM From 2005 to 2020 - Syed Hassan, Syed Najihuddin; Shaari, Siti Nurfatihah (Maʿālim al-Qurʾān wa al-Sunnah, 2021)
Since 2005, the Faculty of al-Quran and Sunnah Studies in Universiti Sains Islam Malaysia (USIM) has published Ma‘alim al-Quran wa al-Sunnah as a trilingual and bi-annual journal. The 16-year-old journal underwent a lengthy process of improvement before obtaining MyCite recognition in 2019. Since its inception, the journal has successfully published a total of 187 quality articles in the field of Quranic and Sunnah studies. This article then examines journal publication statistical data from the first publication in 2005 to 2020. As a result, the quantitative approach to statistically evaluating the findings was chosen as the research method. This study's findings are associated with writing patterns such as writing language, author gender, authors affiliation, writing frequency, and writing field. According to the findings, 408 authors published a total of 186 articles, with the majority of 323 are men. The data also show that 116 articles were in Arabic, 54 articles were in Malay, and the rest were in English. In this journal, single authorship is the most preferred method (92 articles), and the highest page number ratio is 11 to 20 pages (78 articles). Quranic studies account for 53.23% of the articles, and thematic studies are the most popular among authors, accounting for 55 articles. Malaysian authors contribute the most articles (267) followed by Jordanians (41). The authors with the most contributions, 250 in total, were all affiliated with USIM.